Examination of the story of “The Rose of Paracelsus” according to Theory of the Imaginary - Fulya Doğru Şahin (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
This study aims to present an analysis of the images and archetypes in Jorge Luis Borges’s story “The Rose of Paracelsus” (La rosa de Paracelso). In this analysis, we benefit from Carl Gustav Jung’s works on analytical psychology, considered leading sources on symbols and archetypes, and the Theory of the Imaginary of Gilbert Durand. The story is Borges’s second story featuring images of Kabala, and it presents a rose reborn from the ashes through Kabala. In the first part of the study, we explain the concept of archetype making use of Jung’s contributions, and we mention the Theory of the Imaginary, in which Gilbert Durand classifies symbols into two regimes based on reflexes, namely diurnal and nocturnal. Regimes in the theory are associated with verb schemes, adjectives, and nouns related to representations of dominant reflexes. After commenting on the symbolic elements detected in the story according to the theory of Durand, we move on to the use of euphemisms offering a structure of images based on contrasts (antagonism). Since images unaffected by the destructive effect of time and related to the nocturnal regime are detected, it shows that the nocturnal regime prevails. After analyzing two characters of the story according to Jung’s archetypes, we conclude that Paracelsus is identified with the old wise archetype, while Johannes is identified with the shadow archetype. In the light of this, we mention four main conclusions reached in the story. Another conclusion to be reached is that we defeat death and the destructive power of time, achieving immortality through euphemism.